2009
DOI: 10.1007/s11033-009-9857-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and biochemical analysis of the β class carbonic anhydrases in Caenorhabditis elegans

Abstract: The beta class of the carbonic anhydrase (CA) enzyme family has been found in plants, yeast, bacteria and algae, but not in animals. Also, little is known concerning the CAs of C. elegans. Genes possibly encoding beta-CAs were revealed by in silico analysis of the C. elegans genome. Amino acid sequence and 3D structure analysis revealed a resemblance to both plant and cab-type beta-CAs. Temporal expression patterns of the two genes, as well as changes in expression levels under different atmospheric conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 34 publications
0
20
1
Order By: Relevance
“…Fasseas et al [37] state that the 3D structure of their C. elegans β-CA models would resemble archaeal "cab-type" β-CAs, but we cannot agree with their conclusion. In our eyes, the models are nearly identical to the pea BCA (panel a in their Figure 2), and in our hands SwissModel http://swissmodel.expasy.org/ in fact chooses the pea β-CA structure as a template for both insect and nematode β-CAs.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Fasseas et al [37] state that the 3D structure of their C. elegans β-CA models would resemble archaeal "cab-type" β-CAs, but we cannot agree with their conclusion. In our eyes, the models are nearly identical to the pea BCA (panel a in their Figure 2), and in our hands SwissModel http://swissmodel.expasy.org/ in fact chooses the pea β-CA structure as a template for both insect and nematode β-CAs.…”
Section: Discussioncontrasting
confidence: 70%
“…The exception is nematodes, which seem to have two β -CA genes in their genomes. A very recent article [37] reported the cloning and characterization of C. elegans β-CAs and the authors found that one of the two isoforms, BCA-1, has no activity and does not work in complementation assay. This might, however, be due to incorrect sequence: the sequence they show for C. elegans BCA-1 contains the coding sequence of the preceding MTP18 gene fused to the β -CA reading frame.…”
Section: Discussionmentioning
confidence: 99%
“…This class of enzyme has also been discovered in a wide range of taxa, such as yeast ( Saccharomyces cerevisiae ) [34-36], cyanobacteria ( Synechocystis sp. PCC6803) [37], carboxysomes of chemoautotrophic bacteria ( Halothiobacillus neapolitanus ) [38], green algae ( Chlamydomonas reinhardtii ) [39], red algae ( Porphyridium purpureum ) [40], nematodes ( Caenorhabditis elegans) [41], and insects ( Drosophila melanogaster) [4]. While β-CAs were initially thought to be expressed only in plants, this enzyme family is indeed present in a wide variety of species – from bacteria and archaea to invertebrate animals, missing only from vertebrates and most chordates, making it an attractive target for evolutionary studies [5].…”
Section: Introductionmentioning
confidence: 99%
“…The first metazoan β-CAs were reported in 2010 [41]. In one of the studies [4,41], two genes encoding β-CAs (y116a8c.28 and bca-1) were identified in Caenorhabditis elegans .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation